Transparent image access in a distributed picture archiving and communications system: the Master Database Broker...Proccedings of the 16th Symposium for Computer Applications in Radiology. 'PACS: Performance Improvement in Radiology.' Houston TX, May 6-9, 1999 - Cox RD; Henri CJ; Rubin RK (Journal of Digital Imaging)
A distributed design is the most cost-effective system for small-to medium-scale picture archiving and communications systems (PACS) implementations. However, the design presents an interesting challenge to developers and implementers: to make stored image data, distributed throughout the PACS network, appear to be centralized with a single access point for users. A key component for the distributed system is a central or master database, containing all the studies that have been scanned into the PACS. Each study includes a list of one or more locations for that particular dataset so that applications can easily find it. Non-Digital Imaging and Communications in Medicine (DICOM) clients, such as our worldwide web (WWW)-based PACS browser, query the master database directly to find the images, then jump to the most appropriate location via a distributed web-based viewing system. The Master Database Broker provides DICOM clients with the same functionality by translating DICOM queries to master database searches and distributing retrieval requests transparently to the appropriate source. The Broker also acts as a storage service class provider, allowing users to store selected image subsets and reformatted images with the original study, without having to know on which server the original data are stored. Copyright (c) 1999 by W.B. Saunders Company